Male swimmers cross the English Channel faster than female swimmers. Issue 1 (4th November 2012) - Fischer, G.; Knechtle, B.; Rüst, C. A.; Rosemann, T.
<x xml:space="preserve">Abstract</x> We examined the gender difference in performance of open‐water ultra‐swimmers crossing the English Channel between 1875 and 2011. A total of 1606 swimmers (1120 males and 486 females) crossed the English Channel within a mean time of 809.6 ± 175.6 min. The overall female swim time of 796.3 ± 188.7 min was not different compared with the overall male swim time of 815.4 ± 169.4 min (P > 0.05). The fastest male swim time ever of 417 min was 6.7% faster than the fastest female swim time ever with 445 min. The gender difference in performance of the top three times ever was 8.9 ± 2.3%. Over the last 36 years, the performance of the annual top three swimmers showed no changes for both females and males. The top three males (564.3 ± 63.8 min) were significantly faster than the top three females (602.1 ± 58.7 min; P < 0.01). The gender difference remained unchanged at 12.5 ± 9.6% over the years. To summarize, the top three male swimmers in the English Channel were ∼12% faster than the females in the last 36 years. It seems unlikely that female open‐water ultra‐swimmers will overtop males in the near future in the English Channel.